Historiographic Basis of the Research of «School of Action» of V.A.Lay - Lyudmyla Veremiuk (Pedagogical Discourse, 2013)
The author reveals the main ideas of action pedagogics, whose founder is a German pedagogue-reformer W.A.Lay. The author studies historiography of the pedagogical problem «school of action», which is represented in the works of Ukrainian scientists, Ukrainian periodical editions of the end of the XIX – beginning of the XX century, scientific works of of W.A.Lay’s pedagogical heritage written by P.Dudek, T.Kesserling, E.Heineken and the works of modern German scientists C.Hopf, M.Depaepe, U.Carl, H.Flath.